2005
DOI: 10.1590/s0102-311x2005000200003
|View full text |Cite
|
Sign up to set email alerts
|

Análise de dados espaciais em saúde pública: métodos, problemas, perspectivas

Abstract: Studies in which spatial distribution and geographic information systems (GIS) play

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
51

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 76 publications
1
51
0
51
Order By: Relevance
“…9,14 Given the need to increase the understanding of the dynamics of production and transmission of HIV/AIDS infection, instruments traditionally used in GIS can be useful to identify areas with a greater concentration of cases, in addition to enabling the identifi cation of places with higher risk of infection, using statistical models with greater explanatory potential. 1,2,3 The use of georeferenced points in maps allows greater accuracy of analysis, because it is assumed that possible inner differences and inequalities in an area, divided into polygons, will not disappear. Thus, the onset of a disease is the focus, as a result of the demographic and social structure of the city and its differentiation in the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,14 Given the need to increase the understanding of the dynamics of production and transmission of HIV/AIDS infection, instruments traditionally used in GIS can be useful to identify areas with a greater concentration of cases, in addition to enabling the identifi cation of places with higher risk of infection, using statistical models with greater explanatory potential. 1,2,3 The use of georeferenced points in maps allows greater accuracy of analysis, because it is assumed that possible inner differences and inequalities in an area, divided into polygons, will not disappear. Thus, the onset of a disease is the focus, as a result of the demographic and social structure of the city and its differentiation in the country.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, space began to be thoroughly analyzed, bringing important contribution to epidemiological studies and the performance of health services. 2,3 The present study aimed to analyze the spatial distribution of reported AIDS cases in adults and its association with living conditions in the city of Campinas, Southeastern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar dessas limitações, cabe ressaltar que o objetivo deste trabalho não foi o de determinar riscos à mortalidade infantil em nível individual, mas o de descrever os riscos desse tipo de mortalidade relacionados ao contexto social e de infra-estrutura dos municípios do Paraná, com vistas a identificar agregados de sobre-risco 31 , passíveis de intervenção por meio de políticas setoriais ou intersetoriais 31,32 . Nesse sentido, a abordagem feita por estudos ecoló-gicos torna-se mais apropriada 31,32,33 .…”
Section: Discussionunclassified
“…To best understand the differences in the distribution of infectious diseases, ecological studies with spatial data analysis have increased during the past 30 years in Brazil 11 . Different spatial scales were taken into account, usually with geographic and administrative references, such as states and administrative districts.…”
Section: Introductionmentioning
confidence: 99%